Pengaruh Suhu Kalsinasi Terhadap Nilai Rendemen CaO Cangkang Tiram (Crassostrea Gigas) - Lia Handayani; Reza Zuhrayani; Nadia Putri; Riska Nanda (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Oyster shell contained more than 60% of calcium carbonate.it can be used as natural calcium source. Calcium oxide (CaO) can be converted from natural calcium carbonate (CaCO3) at high temperature with decomposition reaction. The purpose of this research was to isolating calcium oxide and to know the yield of CaCO3 decomposition. Calcined samples oyster shells flour is at 500ºC, 700ºC, 900°C and 1100ºC for 2 hours. The sequential data yield of CaO obtained was 96.65%; 96.57%; 60.41% and 54.67%.